2000
DOI: 10.1192/bjp.176.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy, learning disabilities and trauma: new perspectives

Abstract: Practitioners are encouraged to extend their therapeutic repertoire, and to report measurable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 10 publications
5
96
0
3
Order By: Relevance
“…There are indications that besides the cognitive impairments there are other factors making people with ID more vulnerable, including early institutionalization and hospital admissions due to comorbid medical impairments (Tomasulo et al, 2007). Further, it has been argued that understanding oneself as disabled can be traumatizing in itself (Hollins et al, 2000;Levitas, 2001). Thus, the findings of this study support the importance of the potential predisposition of people with ID to development of trauma-related symptoms, due to previous trauma exposure or other vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are indications that besides the cognitive impairments there are other factors making people with ID more vulnerable, including early institutionalization and hospital admissions due to comorbid medical impairments (Tomasulo et al, 2007). Further, it has been argued that understanding oneself as disabled can be traumatizing in itself (Hollins et al, 2000;Levitas, 2001). Thus, the findings of this study support the importance of the potential predisposition of people with ID to development of trauma-related symptoms, due to previous trauma exposure or other vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are indications that early separation from parents through early institutionalization or hospital admissions, fewer previous experiences in managing negative life events, and a limited capacity for gathering social support may make people with ID more vulnerable for the development of PTSD (Tomasulo & Razza, 2007). Moreover, it has been suggested that starting to understand oneself as disabled is potentially traumatizing in itself, thereby being another factor that might contribute to an elevated risk of developing PTSD (Hollins & Sinason, 2000;Levitas, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Psychotherapeutic issues Hollins & Sinason (2000) suggested a number of psychic organising principles, which have to be dealt with in psychotherapy for people with learning disabilities:…”
Section: Psychoanalysis For People With Learning Disabilitiesmentioning
confidence: 99%
“…The existence of disability at birth impacts on the relationship of the individual with their family and community (Hollins & Sinason 2000). There is an increase in emotional disturbance in proportion to the severity of the learning disability (Szivos & Griffiths, 1990).…”
Section: Psychoanalysis For People With Learning Disabilitiesmentioning
confidence: 99%
“…neglect, abuse, exploitation and isolation. 10 In addition parents and families of people with learning disabilities often experience ongoing emotional responses, akin to a bereavement, in trying to accept the loss of the 'perfect child' who has not arrived or has been taken away through illness or accident." These bereavement-type symptoms can be re-kindled at times when previously held expectations for the disabled person are not realised.…”
Section: Psychological Difficultiesmentioning
confidence: 99%